An Online Cross-Sectional Survey on Oral Healthcare Among School-Age Children During COVID-19 Epidemic in Wuhan, China - Li, Zhen; Li, Yuhong; Liu, Chang; Jiang, Han; Zhang, Chenzheng; Du, Minquan (Frontiers in Medicine, 2021)
Background: Since the outbreak of Coronavirus disease 2019 (COVID-19), the government of China adopted many measures which changed people's lifestyle including oral health-related lifestyle to control the transmission. The aim of this study was to investigate oral health status, oral healthcare behaviors, and parental attitudes toward oral healthcare among school-age children in Wuhan during the COVID-19 outbreak and what the status would be when the outbreak is under control. Methods: This study was an online cross-sectional survey facing elementary school students in Wuhan. The questionnaire was completed by children's parents or other family members. The information on demographic data, oral health status, oral healthcare behaviors, and parental attitudes toward oral healthcare was collected at the end of school closure. The chi-square test was used to test the association of different questionnaire items. Results: A total of 18,383 subjects aged 6–13 years with complete data were included in this investigation, and 44.2% of them suffered pain or discomfort related to teeth and gums during the epidemic. While there might be an increasing need and concern of oral healthcare during the outbreak and even when the outbreak was controlled, the worry of infection made it difficult for people to meet their demands of dental attendance. Conclusion: The risk of cross-infection during the treatment had a negative influence on parental attitudes toward dental attendance. Effective measures should be taken to meet people's demands of dental attendance.